Fundamentals of developing conceptual cost estimation models using machine learning techniques: Selection and measurement of building attributes - Wang, Rui; Hafez, Salleh; Zulkiflee, Abdul Samad; Nabilah Filzah, Mohd Radzuan; Wen, Kok Ching (Malaysian Institute of Planners, 2024)
Ensuring the identification of building attributes is the primary task in developing a machine learning cost estimation model. However, the existing research on building attributes has the following shortcomings: it struggles to categorize building characteristics according to various cost types, and the suggested sets of attributes do not clearly establish measurement standards for these qualities. To address these issues, this study aims to select a set of building attributes suitable for conceptual cost estimation and establishment of measurement standards. Through a two-round process of focused group discussions, this research ultimately identified 13 building attributes that can be collected before the completion of building design. These attributes serve as a basis for assessing completed building projects during the model development phase and for evaluating new projects during the model application phase. This study provides a foundational framework for the development of conceptual cost estimation models, ultimately enhancing the accuracy of machine learning cost estimation models.